Simultaneous removal fluoride and nitrate from water in a batch reactor using Al and Fe anodes and Cu, Steel and Graphite cathodes. - Mohammad Reza Samaei; Razieh Ashoori; Abooalfazl Azhdarpoor; Saeed Yousefinejad (Shiraz University of Medical Sciences, 2018)
Background: Simultaneous existence of excessive amounts of fluoride and nitrate in drinking water can cause health problems for humans. In this study, simultaneous removal of fluoride and nitrate from aqueous solutions was investigated using a combination of electroreduction and electrocoagulation processes in a batch reactor with different electrodes. Methods: In this study, at first, an optimum electrode was selected. Afterward, the effects of different operating parameters such as the current density (12- 36 mA/cm2), initial pH (5.5-8.5), NaCl concentration (0.5-1.5gr/L), and electrolysis time (15-120 min), ) on the removal of fluoride (initial concentration: 6 mg/L) and nitrate (initial concentration: 150 mg/) were evaluated, respectively. Results: The highest efficiency of the concurrent fluoride and nitrate removal with Al-Cu electrode and in optimal experimental conditions of the current density of 36 mA/cm2, pH of 7, NaCl concentration of 1gr/L, and electrolysis time of 90 minutes was obtained 87.04 and 89.70%, respectively. Conclusion: High catalytic activity of the copper cathode resulted in better performance than other cathodes in the simultaneous removal of fluoride and nitrate. Generally, it can be concluded that the electrochemical process can reduce the levels of fluoride and nitrate to the amounts below the WHO standard limits, 1.5 mg/L and 50 mg/L, respectively.